Tarik-Ulur Keterwakilan Perempuan Sebagai Menteri Dalam Kabinet Pemerintahan - Arief, Supriyadi; Rasyid Ridho, Mohamad; Erawan, Moh. Arief (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 9 No 3 (2020), 2020)
In addition to the professionalism element, the portion of certain ministries for the party supporting the presidential candidate will influence the presentation of women's representation as ministers in the government cabinet. This article aims to describe the problematic placement of women as ministers in Indonesia and the effective percentage of representation of women as ministers in a government cabinet. The analysis will be carried out normatively using a statutory, historical, and conceptual approach. The results of the study show that until now, women's representation had been accommodated in every government cabinets. However, there is no fixed number of women as ministers. Women tend to occupy ministries that dealt with nature and social life. Therefore, it can be done a special action (affirmative action) in the form of determining the minimum limit of the number of women's representation in a government cabinet. In addition, the determination of the composition of the government cabinet is also based on the zaken cabinet. Selain unsur profesionalitas, porsi kementerian tertentu bagi partai pengusung calon Presiden akan mempengaruhi presentasi keterwakilan perempuan sebagai menteri dalam kabinet pemerintahan. Artikel ini bertujuan untuk menguraikan problematika penempatan perempuan sebagai menteri di Indonesia dan presentase efektif keterwakilan perempuan sebagai menteri dalam suatu kabinet pemerintahan. Penelitian ini  menggunakan analisa  secara normatif dengan menggunakan pendekatan perundang-undangan, sejarah serta konseptual. Hasil kajian menunjukkan bahwa hingga saat ini, keterwakilan perempuan telah diakomodir dalam setiap kabinet pemerintahan. Akan tetapi, tidak ada jumlah yang tetap terhadap presentase perempuan sebagai menteri. Perempuan cenderung menempati kementerian yang berhubungan dengan kodrat dan kehidupan sosialnya. Oleh sebab itu, dapat dilakukan suatu tindakan khusus (affirmative action) berupa penentuan batas minimal jumlah keterwakilan perempuan dalam suatu kabinet pemerintahan. Selain itu, penentuan komposisi kabinet pemerintahan juga harus didasarkan pada kabinet zaken.